2012
DOI: 10.1103/physrevd.85.092017
|View full text |Cite
|
Sign up to set email alerts
|

Observation and study of the baryonicB-meson decaysBD(*)pp¯

Abstract: We present results for B-meson decay modes involving a charm meson, protons, and pions using 455×10 6 BB pairs recorded by the BABAR detector at the SLAC PEP-II asymmetric-energy e + e − collider. The branching fractions are measured for the following ten decays:, and B − →D * + ppπ − π − . The four B − and the two five-body B 0 modes are observed for the first time. The four-body modes are enhanced compared to the three-and the five-body modes. In the three-body modes, the M (pp) and M (D ( * )0 p) invariant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…It has been observed that, despite the phase space expectation, many three-body decays to one baryonantibaryon pair plus an accompanying meson have larger rates than their two-body counterpart, which is the decay to the same baryon-antibaryon pair but with no other particles in the final state, e.g., [11]. Also, some three-body decays are suppressed compared to the fourbody case [12,13]. The phenomenological approaches describe these observations in terms of gluonic and fragmentation mechanisms [14] and pole models [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that, despite the phase space expectation, many three-body decays to one baryonantibaryon pair plus an accompanying meson have larger rates than their two-body counterpart, which is the decay to the same baryon-antibaryon pair but with no other particles in the final state, e.g., [11]. Also, some three-body decays are suppressed compared to the fourbody case [12,13]. The phenomenological approaches describe these observations in terms of gluonic and fragmentation mechanisms [14] and pole models [15].…”
Section: Introductionmentioning
confidence: 99%
“…Baryonic decays of B mesons provide good opportunities to study the mechanism of baryon production and to search for excited baryon resonances [13][14][15]. The observation of intriguing behavior in the baryonic decays of the B 0 and B þ mesons, e.g., the enhancements of the rate of multibody decays and the production of baryon pairs of low mass [16][17][18][19][20][21][22], has further motivated this study.…”
mentioning
confidence: 99%
“…This phenomenon is known as threshold enhancement and describes the dynamically enhanced decay rate at the baryon-antibaryon-mass threshold. It has been observed in baryonic B decays with open charm final states [5][6][7][8], charmless baryonic B decays [9] and in the decay J=ψ → γpp [10]. An example where the decay with the smaller PS is preferred is the ratio of…”
mentioning
confidence: 99%